Mechanotransduction for therapeutic approaches: Cellular aging and rejuvenation - Han, Hye-Min; Kim, Su-Yeon; Kim, Dong-Hwee (AMER INST PHYSICS, 2025)
Mechanotransduction regulates cytoskeletal remodeling, nuclear mechanics, and metabolic adaptation, which are central to cellular aging and rejuvenation. These responses restore mechanical balance in aged cells, reprogram longevity-related gene expression, and alleviate age-related disorders, including neurodegeneration, musculoskeletal decline, and cardiovascular dysfunction. These insights indicate that mechanotransduction is pivotal in cellular and systemic processes underlying aging. The key signaling pathways, including the Hippo/Yes-associated protein (YAP), mechanistic target of rapamycin (mTOR), and transforming growth factor-beta (TGF-beta)/Smad, have been explored in mediating age-related physiological decline, showing potential as therapeutic targets. Aging-dependent stiffening of the extracellular matrix (ECM) is associated with accelerated senescence. Interventions targeting ECM remodeling, such as mechanochemical therapies and nanoparticle delivery systems, provide promising strategies for counteracting cellular deterioration. Research progress has elucidated the critical role of mechanotransduction in organ-specific aging, enabling targeted interventions that align mechanical and biochemical therapeutic strategies. This review highlights the integration of mechanical modulation into therapeutic approaches, emphasizing its potential to restore cellular functionality, improve health, and extend lifespan. Advances in mechanomedicine have opened innovative frontiers in combating aging and age-associated diseases by addressing the interplay between mechanical forces and cellular processes. Cellular rejuvenation-the restoration of aged cells to a functionally younger state through the regulation of mechanotransduction pathways-involves the reversal of senescence-associated phenotypes, including nuclear deformation, mitochondrial alterations, and ECM stiffness. Furthermore, mechanotransduction plays a critical role in cellular rejuvenation by modulating YAP/TAZ activity, promoting autophagy, and maintaining cytoskeletal integrity. (c) 2025 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution-NonCommercial 4.0International (CC BY-NC) license